Unexpected diagnosis of uterine perivascular epithelioid cell tumors: a case report - Di Prospero, Filiberto; Battistoni, Silvia; Bonetti, Monica; Bianconi, Elisabetta; Castelletti, Gabriele (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine perivascular epithelioid cell tumor (PEComa) is a rare mesenchymal tumor. Most PEComas are benign and patients have good prognosis but sometimes they can have aggressive malignant and metastatic potential. Symptoms are nonspecific and similar to those of other uterine tumors. Correct preoperative diagnosis is rarely achieved due to the presence of nonspecific imaging features. At the present time, surgery is the main treatment and adjuvant chemotherapy is used in malignant cases, with different prognosis for each individual case. This case report describes a 42-year-old Caucasian woman presenting to us with a suspected intramural uterine fibroid, menometrorrhagia and iron deficiency anemia (IDA). At the last check-up, an increase in the volume of the known fibroid was observed on transvaginal ultrasound, which measured 72.6×46.8×70.8 mm. The patient underwent a laparotomic myomectomy for suspected enlarged uterine leiomyoma with elevated tumor markers (LDH and CA-125). Histological examination of the surgical specimen revealed a PEComa of uncertain malignant potential. Following this diagnosis, a total hysterectomy with bilateral adnexectomy was performed with histological examination that confirmed the radicalization of the previous surgery without residual tumor tissue. PEComas of the uterus are rare mesenchymal neoplasms that pose significant diagnostic challenges pre-operatively due to their nonspecific imaging features and no specific Blood Markers. This underscores the importance of including PEComa in the differential diagnosis of uterine tumors to ensure optimal surgical planning and patient outcomes.